1991
DOI: 10.2337/diacare.14.7.571
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Subcutaneous Soluble Human Insulin and Insulin Analogues (AspB9, GluB27; AspB10; AspB28) on Meal-Related Plasma Glucose Excursions in Type I Diabetic Subjects

Abstract: Plasma profiles of the insulin analogues were more physiological than that of human insulin after subcutaneous injection. All three analogues given immediately before the meal are at least as effective as soluble human insulin given 30 min earlier. These analogues are promising potential candidates for short-acting insulins of the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
2

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 0 publications
3
38
0
2
Order By: Relevance
“…Subsequent studies confirmed that the rapid rate of absorption from the subcutaneous injection depot seen in pigs also occurred both in healthy volunteers and in patients with type 1 diabetes [14,15]. In a long-term double-blind, randomised crossover study with treatment periods of 2 months involving 21 male patients with type 1 diabetes, insulin X10 was shown to have a more physiological plasma profile than soluble human insulin [16].…”
Section: The Development Of Insulin X10mentioning
confidence: 56%
“…Subsequent studies confirmed that the rapid rate of absorption from the subcutaneous injection depot seen in pigs also occurred both in healthy volunteers and in patients with type 1 diabetes [14,15]. In a long-term double-blind, randomised crossover study with treatment periods of 2 months involving 21 male patients with type 1 diabetes, insulin X10 was shown to have a more physiological plasma profile than soluble human insulin [16].…”
Section: The Development Of Insulin X10mentioning
confidence: 56%
“…Recent studies have revealed beneficial effects of acute and long-term (8 weeks) intranasal administration of regular human insulin (RH-I) on declarative memory in humans (Benedict et al, 2004;Reger et al, 2006). As RH-I molecules tend to self-associate into dimeric, tetrameric, and hexameric units, their absorption after subcutaneous administration is delayed (Kang et al, 1991). In the insulin analog insulin aspart (ASP-I), the amino-acid proline in position B28 is replaced by aspartic acid, reducing the tendency of the insulin molecule to self-associate (Brange et al, 1990;Brange and Volund, 1999), whereas the binding profile to the insulin receptor is the same as of RH-I (Kurtzhals et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…2). Relative to regular human insulin (100 ± 17 %) the plasma glucose area under the curve for the analogue was 51 ± 16 % (p < 0.02) [17]. Because of the more rapid decline in serum hormone concentrations one might also expect the risk of late hypoglycaemia to be reduced with the monomeric analogues.…”
Section: Fast-acting Monomeric Insulinsmentioning
confidence: 91%
“…Studies in insulin-dependent diabetic patients have demonstrated the beneficial pharmacokinetics and significant therapeutic value of monomeric insulin analogues [7,[16][17][18][19]. They yield a degree of glycaemic control, when injected just before a meal, at least comparable to that of human insulin administered 30 min before the meal [7,17]. Administration of insulin analogue Asp B28 resulted in a substantial reduction in the postprandial glucose excursion compared with that of human insulin injected 30 min earlier (Fig.…”
Section: Fast-acting Monomeric Insulinsmentioning
confidence: 99%